Humberside enhanced resettlement service (HERS) evaluation report - Atkinson, John (Probation journal, 2025)
The Humberside Enhanced Resettlement Service (HERS) was a psychologically informed, supported accommodation service for people on probation whose presentation is consistent with personality disorder. An evaluation, utilising semi-structured interviews, identified four themes of experience for people on probation and their probation practitioners who worked with HERS: (1) relationships; (2) practical support; (3) expectations, and (4) risk. This suggested that providing psychologically led supported accommodation enhances therapeutic relationships between professionals and people on probation, which may assist in reducing reoffending. Conclusions are tentative due to methodological limitations and future research should employ more robust methods to assess the impact of similar psychologically informed supported accommodation projects.